Feasibility Analysis of Hybrid Corn Farming in Sindangkasih Village, West Ranomeeto Subdistrict, South Konawe Regency - Rinda Deswita Rustam; Lukman Yunus; Abdul Gafarudin (International Journal of Technology and Education Research, 2026)
This study aims to analyze the income and feasibility of corn farming in Sindangkasih Village, Ranomeeto Barat District, Konawe Selatan Regency using a quantitative descriptive method with a census technique involving 45 farmers as respondents. Data were collected through observation, interviews, and documentation, and analyzed using income analysis, Revenue Cost Ratio (R/C), and Break Even Point (BEP). The results showed that the total revenue of corn farming was Rp1,821,307,143 per year with an average of Rp40,473,492 per farmer, while the total production cost was Rp589,724,960 with an average of Rp13,104,999 per farmer, resulting in a total income of Rp1,231,582,183 per year with an average of Rp27,368,493 per farmer or Rp39,835,359 per hectare. The R/C ratio value of 3.1 indicates that the farming is profitable, while the BEP production value of 339 kg and BEP revenue of Rp1,263,000 are lower than the average production of 4,576 kg and average revenue of Rp40,473,492, indicating that corn farming operates above the break-even point and has good prospects for further development in increasing farmers’ income and welfare